Outsourcing flexibility under financial constraints - Choi, Jongmoo Jay; Ju, Ming; Trigeorgis, Lenos; Zhang, Xiaotian Tina (Journal of Corporate Finance, 2021)
We posit that outsourcing flexibility helps overcome financial constraints and provide evidence concerning the role of financial constraints and its interaction with operational flexibility on the likelihood and market value of outsourcing. We find that the likelihood of outsourcing is higher the greater the firm's financial constraints prior to outsourcing and that the effect of financial constraints on the likelihood of outsourcing is greater the lower the ex-ante operational flexibility, suggesting partial substitution between financial and operational flexibility. We further show that the market value impact of outsourcing announcements is predominantly positive confirming net flexibility gains positively related to ex-ante financial constraints. Our findings suggest that outsourcing is a vehicle for flexibility acquisition and that financial constraints play a prominent role.